Recent Progress in the Development of Aromatic Polymer-Based Proton Exchange Membranes for Fuel Cell Applications - S., Raja Rafidah R. (Polymers (Basel), 2020)
Proton exchange membranes (PEMs) play a pivotal role in fuel cells; conducting protons from the anode to the cathode within the cell’s membrane electrode assembles (MEA) separates the reactant fuels and prevents electrons from passing through. High proton conductivity is the most important characteristic of the PEM, as this contributes to the performance and efficiency of the fuel cell. However, it is also important to take into account the membrane’s durability to ensure that it canmaintain itsperformance under the actual fuel cell’s operating conditions and serve a long lifetime. The current state-of-the-art Nafion membranes are limited due to their high cost, loss of conductivity at elevated temperatures due to dehydration, and fuel crossover. Alternatives to Nafion have become a well-researched topic in recent years. Aromatic-based membranes where the polymer chains are linked together by aromatic rings, alongside varying numbers of ether, ketone, or sulfone functionalities, imide, or benzimidazoles in their structures, are one of the alternatives that show great potential as PEMs due totheir electrochemical, mechanical, and thermal strengths. Membranes based on these polymers, such as poly(aryl ether ketones) (PAEKs) and polyimides (PIs), however, lack a sufficient level of proton conductivity and durability to be practical for use in fuel cells. Therefore, membrane modifications are necessary to overcome their drawbacks. This paper reviews the challenges associated with different types of aromatic-based PEMs, plus the recent approaches that have been adopted to enhance their properties and performance.